Survival Analysis of Newborns with Low Birth Weight (Very and Extremely Low) in Kyrgyzstan - Tabyshova, Ainura; Uzakbaev, Kamchibek; Abduvalieva, Sagynbu; Ahmedova, Damira; kyzy, Begimai Muktarali (International Journal of Child Health and Nutrition, 2026)
Purpose: The increase in the number of premature births in the Kyrgyz Republic was accompanied by the growth of the proportion of newborns with very low (VLBW) and extremely low birth weight (ELBW), which required a systematic analysis of the survival. The study aimed to determine the dynamics of survival among newborns in these groups for 2019-2024, accounting for regional differences. Material and Methods: Kaplan-Meier curves and the log-rank test were used to assess statistical significance. Data, including medical records, reports from perinatal centres, and official statistics from the National Statistical Committee of the Kyrgyz Republic, were collected from all regions of the country, with an emphasis on regional differences in neonatal care infrastructure. Results: The survival of newborns weighing 1,000 to 1,499 grams increased from 23.4% to 51.8%, accompanied by a reduction in early neonatal mortality from 48% to 26%. Among children weighing less than 1,000 grams, survival increased from 2.2% to 8.6%, at remained low. It was established that the most pronounced improvement was observed in the southern regions of the country, whereas in the northern and mountainous areas, the lag remained. The main factors driving positive dynamics were the expansion of antenatal care, the equipping of hospitals with intensive care equipment, and improvements in staff qualifications. Conclusion: The practical significance of the study lies in the justification for further development of neonatal care infrastructure to reduce infant mortality and balance regional differences in Kyrgyzstan.